EFEKTIVITAS VIDEO ANIMASI DALAM PEMBELAJARAN HAK DAN KEWAJIBAN WARGA NEGARA - Hardi Abdul Hakim; Ramadhani Rahelia R.S; Yola Azila Nafrianti; Ferdi Mahendra; Diaz Sari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the effectiveness of the use of animated videos in Civic Education (PKn) learning on the rights and obligations of citizens in grade IV of SD IT Esa Unggul. The background of the research departs from the problems of PKn learning which are still verbal and abstract so that students have difficulty understanding the basic concepts of citizenship. The research approach used a descriptive qualitative method with the subjects of one PKn teacher and 28 students. Data was collected through observation and interviews, then analyzed using Miles and Huberman's interactive model which included data reduction, data presentation, and conclusion drawn. The results of the study showed that animated videos improved learning activities, attention focus, and emotional responses of students. This visual medium helps to concretize abstract concepts, facilitates understanding, and encourages active participation through discussions after video screening. The findings are in line with visual communication theory, agenda setting, and uses and gratifications that explain how media is able to direct attention, provide meaning, and meet students' learning needs. Nonetheless, technical barriers such as internet connection and video duration require the active role of teachers in facilitating learning to remain effective. The research concludes that animated videos are an effective learning medium to increase students' understanding and activeness on the rights and obligations of citizens, and are relevant to the demands of the Independent Curriculum which emphasizes the use of technology and more interactive learning.